Development of a balanced menu based on local food of Southwest Papua with serving the contents of my plate as an effort to improve consumption patterns of stunting children - Florensia, Wilma; Supu, La (Science Midwifery, 2023)
People need to know that many natural healthy foods come from local foods with high nutritional value to prevent various nutritional problems. The general aim of this research is to develop a balanced menu based on local Southwest Papuan food with the contents of Piringku as an effort to improve the consumption patterns of stunted children. The type of research used is experimental with a development research method approach. Research was carried out to prepare a 7-day food menu pattern using a local food menu based on balanced nutrition and to test the effectiveness of the product.This local food-based menu is made on a 7-day cycle to avoid boredom and refers to the dietary requirements of children under five, namely providing adequate nutrients for body growth and development. From the results of the hedonic test, it was found that the 7-day menu based on local food from Southwest Papua was varied, the portions were appropriate, the colors were attractive, liked, the taste was good and the texture was appropriate.